Inferring mating behavior and reproductive success of (Agkistrodon contortrix) using molecular parentage assignment tests - Kendall, Jennifer, author; Savidge, Julie A., advisor; Douglas, Michael E., advisor; Douglas, Marlis R., committee member; Richards, Christopher, committee member; Givens, Geoffrey, committee member (Colorado State University. Libraries, 2012)
Historically, behavioral and ecological research on snakes has been limited due to the secretive and cryptic nature of these species. Readily available molecular techniques have enhanced the study of reproductive behavior and advanced our understanding of mating patterns (such as multiple paternity) that were previously deemed ambiguous. Instead they have been revealed as often prevailing and strongly influential on genetic population structure. Underlying biological questions about the social and behavioral movements associated with mating can be addressed by correlating the results of population genetic analyses with known social structure and can be used to make inferences regarding landscape genetics and gene flow. During a three-year (2001--2003) ecological study of a geographically isolated population of Northern Copperhead (Agkistrodon contortrix) in Meriden, Connecticut, U.S.A., blood samples from 254 individuals (117 adults and 137 juveniles) were collected for extraction and amplification of genomic DNA. Five microsatellite DNA markers, derived from species closely related to the study organism, were used to identify individuals in the population and to infer paternity. These analyses revealed aspects of mate selection, reproductive ecology, and sociality in Northern Copperhead. No spatial genetic structure among dens could be determined with the available data and thus influence of den structure on mating patterns could not be inferred. In contrast, genetic structure in the form of three distinct genetic clusters was identified within the population. Paternity tests identified a nonrandom mating pattern by which individuals showed a clear pattern of intra-cluster mating. Causation underlying this phenomenon remains unclear, as further ecological and genetic data would be needed.
Keywords: parentage assignment; mating behavior; Agkistrodon contortrix